Correlation based rotation-invariant corner detector - Mazzaferri, J. (2008)
In this work we introduce a new approach for corner extraction. The method that allows the corner extraction with rotation invariance is composed by a spiral phase function and a binary amplitude. The designed function can be easily implemented as a filter for a Vander Lugt-like optical correlator. A final image obtained with the detector presents intensity peaks in each corner location. Numerical simulation has been performed on a set of synthetic scenes, modulated either in amplitude or phase. Results that show the very good performance of the method are shown. © 2008 American Institute of Physics.